2018
DOI: 10.17584/rcch.2018v12i1.7335
|View full text |Cite
|
Sign up to set email alerts
|

Tolerancia a la salinidad de <i>Passiflora tarminiana</i> Coppens & Barney

Abstract: Passiflora tarminiana es una glicofita trepadora, nativa de la región andina que tiene tolerancia a la salinidad y estrés hídrico moderado. El objetivo de este estudio fue evaluar la capacidad para la excreción de sodio como una posible estrategia de esta especie para la tolerancia a la salinidad y a la sequía. La excreción de sal y las concentraciones de iones excretados se examinaron en plantas cultivadas durante siete meses bajo varios niveles de salinidad [(NaCl) 2,5; 4,0 y 5,5 dS m-1 (25, 40 y 55 mM)] y d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
(12 reference statements)
0
6
0
1
Order By: Relevance
“…The presence of leaf trichomes and numerous leaf and petiolar glands in this species (Crochemore et al, 2003;Silva et al, 2013) possibly facilitate salinity tolerance. These structures, glands, papillae and trichomes, allow tolerance to excess salts through the salt exclusion mechanism (Hurtado-Salazar et al, 2018), as sodium exclusion or leaf tissue tolerance contribute to salinity tolerance (Kotula et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of leaf trichomes and numerous leaf and petiolar glands in this species (Crochemore et al, 2003;Silva et al, 2013) possibly facilitate salinity tolerance. These structures, glands, papillae and trichomes, allow tolerance to excess salts through the salt exclusion mechanism (Hurtado-Salazar et al, 2018), as sodium exclusion or leaf tissue tolerance contribute to salinity tolerance (Kotula et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Strategies that enable the maintenance of agricultural activity, such as the use of tolerant materials, are essential. Tolerance to abiotic and biotic factors can be found in wild species (Silva et al, 2017;Hurtado-Salazar et al, 2018), but these generally have lower yield than those cultivated, in addition to production characteristics not accepted by the market. Therefore, wild species have been studied for their potential to be used as rootstocks (Silva et al, 2018a;Souto et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Modifications in the root system occur because the root volume increases under water stress conditions, which favors water uptake and decreases the aerial part in order to reduce the rate of leaf transpiration (Rodríguez et al, 2019). Nevertheless, Hurtado-Salazar et al (2018) found that the accession m15 (P. tarminiana) may be able to survive with salinity up to 5.5 dS m -1 (NaCl), which is high, with the removal of toxic ions. Possibly, the excretion of excess salt was done through epidermal glands.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is hard to clearly define the effect of soil salinity, since the damages caused by salt to plants depend on the species, genotype, growth stage, exposure time, environment and amount and nature of the salts, and also requires the use of tolerant material when applying salt water to agricultural crops (Munns and Gilliham 2015;Dogan, 2020). In most cultivated plants, salinity, drought and water deficit sensitivity are associated with the inability to prevent and/or tolerate high concentrations of salts (Hurtado-Salazar et al 2018).…”
Section: Introductionmentioning
confidence: 99%